A toxic organic solvent-free technology for the preparation of PEGylated paclitaxel nanosuspension based on human serum albumin for effective cancer therapy - Yin TJ (Dove Medical Press, 2015)
Tingjie Yin,* Lihui Dong,* Bei Cui, Lei Wang, Lifang Yin, Jianping Zhou, Meirong Huo State Key Laboratory of Natural Medicines, Department of Pharmaceutics, China Pharmaceutical University, Nanjing, People’s Republic of China *These authors contributed equally to this work Abstract: Clinically, paclitaxel (PTX) is one of most commonly prescribed therapies against a wide range of solid neoplasms. Despite its success, the clinical applicability of PTX (Taxol®) is severely hampered by systemic toxicities induced by Cremophor EL. While attempts to bypass the need for Cremophor EL have been developed through platforms such as Abraxane™, nab™ relies heavily on the use of organic solvents, namely, chloroform. The toxicity introduced by residual chloroform poses a potential risk to patient health. To mitigate the toxicities of toxic organic solvent-based manufacture methods, we have designed a method for the formulation of PTX nanosuspensions (PTX-PEG [polyethylene glycol]-HSA [human serum albumin]) that eliminates the dependence on toxic organic solvents. Coined the solid-dispersion technology, this technique permits the dispersion of PTX into PEG skeleton without the use of organic solvents or Cremophor EL as a solubilizer. Once the PTX-PEG dispersion is complete, the dispersion can be formulated with HSA into nanosuspensions suitable for intravenous administration. Additionally, the incorporation of PEG permits the prolonged circulation through the steric stabilization effect. Finally, HSA-mediated targeting permits active receptor-mediated endocytosis for enhanced tumor uptake and reduced side effects. By eliminating the need for both Cremophor EL and organic solvents while simultaneously increasing antitumor efficacy, this method provides a superior alternative to currently accepted methods for PTX delivery. Keywords: human serum albumin, nanosuspension, paclitaxel, polyethylene glycol, solid-dispersion technology